Radical Oxygen Species, Oxidized Low-Density Lipoproteins, and Lectin-like Oxidized Low-Density Lipoprotein Receptor 1: A Vicious Circle in Atherosclerotic Process - Marco Munno; Alice Mallia; Arianna Greco; Gloria Modafferi; Cristina Banfi; Sonia Eligini (MDPI AG, 2024)
Atherosclerosis is a complex condition that involves the accumulation of lipids and subsequent plaque formation in the arterial intima. There are various stimuli, cellular receptors, and pathways involved in this process, but oxidative modifications of low-density lipoprotein (ox-LDL) are particularly important in the onset and progression of atherosclerosis. Ox-LDLs promote foam-cell formation, activate proinflammatory pathways, and induce smooth-muscle-cell migration, apoptosis, and cell death. One of the major receptors for ox-LDL is LOX-1, which is upregulated in several cardiovascular diseases, including atherosclerosis. LOX-1 activation in endothelial cells promotes endothelial dysfunction and induces pro-atherogenic signaling, leading to plaque formation. The binding of ox-LDLs to LOX-1 increases the generation of reactive oxygen species (ROS), which can induce LOX-1 expression and oxidize LDLs, contributing to ox-LDL generation and further upregulating LOX-1 expression. This creates a vicious circle that is amplified in pathological conditions characterized by high plasma levels of LDLs. Although LOX-1 has harmful effects, the clinical significance of inhibiting this protein remains unclear. Further studies both in vitro and in vivo are needed to determine whether LOX-1 inhibition could be a potential therapeutic target to counteract the atherosclerotic process.